The influence of the German Geographic School on international schools and its role in field research and geographical statements: (Western Pacific region( - Al-Dulimi, Kamal Abdullah Hasan; Al-Mashhadani, Marwa Mahrous Nassar (Al-Adab Journal, 2020)
With all the discussions that the German geography witnessed in order to develop it, it still suffers from ambiguity and turmoil in understanding its subject, and this situation continued until before the First World War. However, this does not diminish the edifice constructed by the German Geographic School, as it is a tall and prominent landmark on the path of geographical thought. Geography has reached the level of fundamental science that examines human and natural laws and phenomena in various scientific ways, since all the credit is due to the German geographic school to the two worlds (Humboldt and Ritter) who contributed to establishing modern scientific rules and elevated them to the level of organized fundamental science that derives its data It is directly from nature, using inductive approaches that are appropriate to the scientific method at that time. As geography has shifted from a collection of general descriptive information about nature and people to a philosophical field based on analysis and observation.